Enhanced UE slice availability and mobility through multi‐connectivity in 5G multi‐RAT networks. Issue 6 (14th July 2020) - Nayak Manjeshwar, Akshatha; Jha, Pranav; Karandikar, Abhay; Chaporkar, Prasanna
Abstract : Fifth Generation (5G) mobile networks utilize network slicing for providing diverse services over a shared infrastructure. User Equipments (UEs) can access multiple slices concurrently to avail services requiring different Quality of Service (QoS). Third Generation Partnership Project (3GPP) 5G stipulates that all slices supported for a given UE should be deployed homogeneously over its Registration Area (RA) for ensuring slice availability during mobility. 3GPP also prescribes mechanisms such as multi‐connectivity for improving mobility robustness in heterogeneous networks. However, to the best of our knowledge, the role of multi‐connectivity in the context of network slicing has not been well‐explored. In this paper, we propose using multi‐connectivity for improving the availability of network slices. 1 Abstract : Mobile devices in Fifth Generation (5G) networks can avail diverse services concurrently through access to multiple logical networks (network slices). In this paper, we propose to improve slice coverage and availability in mobile networks through the usage of multi‐connectivity, a mechanism to connect a mobile device to more than one base station simultaneously. We also propose enhancements to Third Generation Partnership Project (3GPP) multi‐connectivity protocol for improved slice availability in the network.